2018
DOI: 10.1159/000493336
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnosis in Nonlymphoproliferative Malignant Pleural Effusion Cytopathology and Its Correlation with Patients’ Demographics

Abstract: Background: We report our experience with malignant pleural effusion (MPE) and the impact of patients’ demographics on the differential diagnosis at the primary site. Methods: After IRB approval, we searched our pathology database from January 2013 to January 2017 for patients with positive pleural effusions (PEs). Patients’ demographics and clinical histories were noted. Results: 474 patients were identified (288 females [61%] and 186 males [39%]), ranging in age from 19 to 64 years old. Ethnicity was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Adenocarcinoma of the lung was the most common primary neoplasm involving the pleura in our cohort, followed by clear cell renal, colorectal and breast carcinomas, in accordance to previously published series . Interestingly, negative pleural effusions followed by positive pleural biopsies were more common in men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Adenocarcinoma of the lung was the most common primary neoplasm involving the pleura in our cohort, followed by clear cell renal, colorectal and breast carcinomas, in accordance to previously published series . Interestingly, negative pleural effusions followed by positive pleural biopsies were more common in men.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study by the authors, women were diagnosed more frequently with a positive pleural effusion (61%) than men. This could be partly explained in that study by the high prevalence of tumours from breast and gynaecological origin, which showed a low incidence in the current dataset . Also, a high proportion of metastatic sarcomas was present among the false‐negative pleural effusion samples when taking into account the overall incidence of sarcomas involving effusions reported in the literature .…”
Section: Discussionmentioning
confidence: 63%
“…In a study examining the demographic data of 474 patients with malignant PE, approximately 85% of the patients diagnosed with malignant cytology were over 50 years of age, which was similar to our findings (12).…”
Section: Discussionsupporting
confidence: 88%
“…According to the literature, cutaneous melanoma is known to metastasize to the lung; however, little is known about metastasis limited to the pleura given that this is an exceedingly rare event . The mechanism of tumor localization to the pleura and prognosis of such patients is not known.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, cutaneous melanoma is known to metastasize to the lung; however, little is known about metastasis limited to the pleura given that this is an exceedingly rare event. 6 The mechanism of tumor localization to the pleura and prognosis of such patients is not known. A cytomorphologic diagnosis of metastatic melanoma using effusion cytology is very difficult because malignant effusions associated with metastatic melanoma may exhibit a variable cytological appearance.…”
Section: Cytopathologic Findingsmentioning
confidence: 99%